New Tools for Theuth’s Myth - Arena, Marinella (Urban, 2016)
Introduction Socrates encourages knowledge that comes from oral communication between men who live in the city. And he evokes the Egyptian divinity, Theuth, to give more importance to his argument. The myth recounts that Theuth, after inventing writing, gifted it to the Egyptians. King Thamus admonishes him, underlining the fact that this new kind of communication will reduce the capacity of memory. The complexity of the city has always been in balance between unity and multiplicity, order and chaos, memory and nemesis, stereotype and peculiarity. Today we have many new tools for increasing the knowledge of cities: multimedia informatic systems; 3D reconstructions, and the so-called Web 3.0 We can observe every point of the globe but the enormous quantity of data leaves us without the memory of places that are useful for the comprehension of the phenomena. The virtual city, or the labyrinth of the perception, reveals itself only when observed from the sky, while we are wearing Daedalus’ wings or potent lenses of a satellite? The challenge of our days, maybe, is to design critical structures able to give an organic and well define vision of the city. Only in this way will it be possible to define a city as a specific “Place”. Keywords Representation; web; city; elusive vision; automatic